TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN BANTUAN LANGSUNG TUNAI- DANA DESA DALAM MEWUJUDKAN GOOD VILLAGE GOVERNANCE DI DESA LAU BAKERI KECAMATAN KUTALIMBARU - Yessi Apricilia Saragi; Erika Revida (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The implementation of good village governance is essential to ensure that village financial management is transparent, accountable, and oriented toward community welfare. Direct Cash Assistance–Village Funds (BLT-DD) are government programs intended to support poor and vulnerable households at the village level. However, discrepancies often occur between the intended objectives and actual implementation. This study aims to analyze the transparency and accountability of BLT-DD management in Lau Bakeri Village, Kutalimbaru District. Using a qualitative descriptive method with a case study approach, data were collected through in-depth interviews, observation, and documentation involving village officials, beneficiaries, and non-beneficiaries. The analysis refers to transparency indicators by Christopher Hood, including openness of information, accessibility, and clarity of financial reporting; and accountability indicators by Mulgan, emphasizing responsibility and justification of actions. The results show that BLT-DD management in Lau Bakeri Village remains suboptimal. Transparency is low due to the absence of published recipient lists, limited access to information, and unclear financial reporting. Accountability also lacks effectiveness, as indicated by inconsistencies between publicly stated budget allocations and the actual amounts received by residents. The limited number of BLT-DD recipients (17 people per 3-month period) does not reflect the real socioeconomic conditions, where most villagers earn below the poverty threshold. Strengthening information disclosure, improving data verification, and ensuring consistent budget reporting are required to advance good village governance.